THE EFFECT OF A REALISTIC MATHEMATICS EDUCATION ON THE PROBLEM-SOLVING ABILITY OF MATHEMATICS - Dewi Soraya; Jupriyanto Jupriyanto; Yunita Sari (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the positive effect of using the Realistic Mathematics Education (RME) model on the learning outcomes of problem-solving math story problems for second-grade students of SDN 03 Pelang. The lack of students understanding of the issue of the story problems and imagining the problems in story questions is not optimal. The RME model will provide students with authentic experiences and opportunities to construct mathematical knowledge. The type of research conducted is experimental research. The design used in this study is quasi-experimental in the form of a nonequivalent control group design. The subjects in this study were second-grade students of SDN 03 Pelang. The data collection technique in this research is in the form of a test (description). While the data analysis techniques include analysis of instrument trials, prerequisite tests, and hypothesis testing. The results showed a significant effect of the RME learning model on the problem-solving ability of students' story problems between the experimental and control groups. So, the RME makes students actively participate in learning so that students' problem-solving skills are achieved optimally.